Evaluasi User Experience dengan Metode Heuristic Evaluation dan Persona (Studi pada : Situs Web Dalang Ki Purbo Asmoro) - Aditya Kurniawan; Retno Indah Rokhmawati; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Website is one of the media in spreading information, one of them is Ki Purbo Asmoro website. However, some shortages were found by the users when accessing the website. To find out the problems on the website, an analysis of user experience through Heuristic Evaluation method was needed. In addition, to know further about the impression, goals, and expectations of the users in using the website, a Persona as a fictional representation of the potential users of the website was formed. Evaluation was done in 2 stages. The evaluation of the phase 1 was to find problems on the initial website. The evaluation of the phase 2 was to find the problem on the repair prototype that built on the solution to the problems found in phase 1 and Persona evaluations. In the result of the evaluation of the phase 1, the most problems in the heuristic principle found were in the principle of H4 - Consistency and Standards, and on H8 - Aesthetic and Minimalist Design. While in the evaluation of the phase 2 some problems were found on the principle of H4 - Consistency and Standards, and H7 - Flexibility and Efficiency of use. Some improvements were made to decrease the number of problem findings and severity ratings between the two evaluation phases.